Clinical profile of patients with Atrial Fibrillation presenting to cardiac centre at Lumbini province of Nepal - Gautam, Samir; Dhungel, Sachin; K C, Bishal; Khan, Majhar; Shakya, Abhishesh; Panjiyar, Rajesh; Sharma, Deepanjali (Journal of National Heart and Lung Society Nepal, 2026)
ABSTRACT Background: Atrial fibrillation (AF) is the commonest sustained arrhythmia in cardiology practice. It has variable etiology with age based variation in clinical scenario. Stroke is major complication which leads to disability, cost and mortality. Medical management is targeted towards prevention of stroke reducing morbidity and mortality. Methods: This is a cross-sectional observational study conducted at Gautam Buddha Community Heart Hospital at Lumbini province Nepal. Patients with diagnosis of Atrial fibrillation presenting to outpatient department were evaluated. SPSS version 22 was used to analyze data. Results: Among the patients evaluated females were 58% more common than males 42%.Majority 54% patients were of age group more than 65 years, 31% were of the age between 45 to 65 years and 15% were of the age less than 45 years. Rheumatic heart disease was most common association 31% followed by Systemic hypertension 29% and dilated cardiomyopathy 14%. Thyroid disorder was present in 7%, coronary artery disease was found in 5% and degenerative valvular heart disease in 3%. Oral anticoagulant use was present in 84%, antiplatelet use was present in 12%. 7% patient already had stroke. Rate control was present in 94%. Digoxin use was present in 26% and no drug was used for rate control in 5%. Conclusion: Atrial fibrillation becomes more prevalent with age. AF was more common in females. Rheumatic heart disease is still common cause in young population with systemic hypertension more common with advanced age. Oral anticoagulant use is increasing in clinical management of AF.